How Britain Loves the NHS - Stewart, Ellen A. (Policy Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence.It is often claimed that the UK is unusually attached to its National Health Service, and the last decade has seen increasingly visible displays of gratitude and love. While social surveys of public attitudes measure how much Britain loves the NHS, this book mobilises new empirical research to ask how Britain love its NHS.